Deviation of a set of trajectories from the state of equilibrium - Martynyuk, A.A. (Reports of the National Academy of Sciences of Ukraine, 2017)
Estimates of the deviation of a set of trajectories from an equilibrium state are obtained for a family of differential equations. These estimates can be applied to the study of the stability of motion like the case of systems of ordinary diffe rential equatians.